Firm size, factor intensities, protection and the sectoral patterns of West German manufacturing investment in less developed countries - Paulgeorg Juhl (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1978)
It is the purpose of this paper to test the following hypotheses concerning the impact of firm size, factor intensities and protection on the sectoral allocation of West Gentian manufacturing foreign direct investment (FDI) in less developed countries (LDCs): Hyp.I: The branches' propensity to invest in LDCs is the higher, the higher the average size of firm within the respective branches. Hyp.II: The higher a branch's human capital intensity, the lower its propensity to invest in LDCs. Hyp.Ill: Rising physical capital intensity induces increasing FDI in LDCs. Hyp.IV: The higher the branches' imported raw material intensity, the lower their propensity to invest in LDCs. Hyp.V: The higher a branch is protected against competing imports from LDCs, the lower its propensity to relocate production to LDCs.
Keywords: 330